2006
DOI: 10.1007/s11223-006-0086-6
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength of an (α + β)-type titanium alloy Ti-6Al-4V produced by the electron-beam physical vapor deposition method

Abstract: The fatigue test results are presented for an (α β + )-type titanium alloy in the form of two-layered smooth specimens (the first layer is a condensate prepared by the electron-beam physical vapor deposition method, the second one is a substrate from a standard sheet material of the same type) and condensate specimens. It has been found that the presence in the condensate of deposition defects such as droplets lowers the fatigue limit of the material by approximately 1.5 times as compared to that of the conde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…During deposition, some big droplets depart from the surface of the melt, settling in the condensate and forming columns, which grow and reach the condensate surface. These columns are efficient surface stress concentrators and adversely affect on the fatigue resistance characteristics of the Ti-6Al-4V alloy condensate [11]. The investigation of specimen fatigue fracture surfaces revealed that for almost all but three specimens, crack initiation occurred within the concentrator on the condensate surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During deposition, some big droplets depart from the surface of the melt, settling in the condensate and forming columns, which grow and reach the condensate surface. These columns are efficient surface stress concentrators and adversely affect on the fatigue resistance characteristics of the Ti-6Al-4V alloy condensate [11]. The investigation of specimen fatigue fracture surfaces revealed that for almost all but three specimens, crack initiation occurred within the concentrator on the condensate surface.…”
mentioning
confidence: 99%
“…To confirm the validity of the above-proposed model for calculating the fatigue life of specimens with surface notches, fatigue test results for specimens of ) (    -titanium alloy Ti-6Al-4V condensate obtained by the ЕВ PVD method [11] were used. ЕВ PVD coatings of the Ti-6Al-4V alloy were prepared by deposition of the same but cast alloy onto flat substrates.…”
mentioning
confidence: 99%